1987
DOI: 10.1063/1.866080
|View full text |Cite
|
Sign up to set email alerts
|

Wall-pressure fluctuations in turbulent pipe flow

Abstract: Wall-pressure fluctuation measurements are reported for the fully developed turbulent flow of glycerine in a long pipe. Because of the relatively large viscous scales associated with glycerine, it has been possible to perform pressure fluctuation spectral measurements for 0.7≤d+≤1.5, where d+ is the transducer diameter expressed in wall units. The data presented are for d+ values smaller than ever before reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…It is usually possible to refer measurements to some point defined as a constant, but the definition varies among experiments, and complicates comparisons. It may not be a coincidence, for example, that the lowest fluctuations in figure 8(a) correspond to a pipe in which the experimenters took special care to remove low-frequency components and spurious vibrations (Lauchle & Daniels 1987).…”
Section: 'Sterile' Eddies and The Fluctuations Of The Outer Layermentioning
confidence: 99%
“…It is usually possible to refer measurements to some point defined as a constant, but the definition varies among experiments, and complicates comparisons. It may not be a coincidence, for example, that the lowest fluctuations in figure 8(a) correspond to a pipe in which the experimenters took special care to remove low-frequency components and spurious vibrations (Lauchle & Daniels 1987).…”
Section: 'Sterile' Eddies and The Fluctuations Of The Outer Layermentioning
confidence: 99%
“…Acceleration is shown on the left and wall pressure is shown on the right. In addition, two reference pressure sensors were installed in the same axial plane as the most upstream TBL sensor, and were installed 120 ı apart (similar to those of Lauchle and Daniels [2]). The separation distance between the reference pressure sensors and the all TBL pressure sensors results in uncorrelated TBL pressures for all frequencies of interest.…”
Section: Measured Datamentioning
confidence: 99%
“…Lauchle and Daniels [2] employed a related subtraction technique using multiple sensors measured simultaneously to remove noise signals from their measurements of turbulent boundary layer (TBL) wall pressure. Naguib, Gravante, and Wark [3] discuss the advantages of an optimal filtering approach compared to a difference approach.…”
Section: Introductionmentioning
confidence: 99%
“…At low frequencies part of the source signal was cancelled along with the background noise if insufficient transducer spacing was used. It was shown that this undesired source signal cancellation [7] was an order of magnitude smaller than that removed using the aforementioned methods [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…One technique used the assumption that if the background noise at two different transducers was uncorrelated yet statistically equal, the frequency spectrum due to only the model source could be recovered from the difference between the two time-series. Improvements were made on the technique over the next two decades [2][3][4][5]. In 1989, a technique for capturing model noise from turbulent boundary layer wall-pressure fluctuations was investigated [6].…”
Section: Introductionmentioning
confidence: 99%